(untitled) (MAUSAM, 2013)
ok;q foKku os/k’kkyk] lqdqck] tkiku esa 6 ekpZ ls 24 ekpZ 2006 rd MkWclu vkstksu LisDVªksa QksVks ehVj ijLij rqyuk djus ds fy, ,d MCY;w-,e-vks-@th-,-MCY;w- vfHk;ku pyk;k x;kA bl ijLij rqyukRed vfHk;ku ds nkSjku Hkkjrh; ekud MkWclu vkst+ksu LisDVªksQksVksehVj la[;k 112 dh rqyuk ks=h; ekud MkWclu vkstksu LisDVªksQksVksehVj la[;k 116 ds lkFk dh xbZA bu rqyukvksa ls bl ckr dh iqf"V gqbZ gS fd Hkkjrh; MkWCklu vkstksu LisDVªksQksVksehVj la[;k 112 va’kkdu dh lgh fLFkfr esa Fkk vkSj midj.k ls izkIr vk¡dM+sa lgh FksA 36 ds lkFk 112 ls izkir ifj.kke Hkh ,d nwljs ls lgh esy [kk jgs gSaA The WMO/GAW campaign for inter-comparison of Dobson Ozone Spectrophotometer was held from 6 to 24 March 2006 at the Aerological Observatory, Tsukuba, Japan. During the inter-comparison campaign, the Indian standard Dobson Ozone Spectrophotometer no.112 was compared with the regional standard Dobson Ozone Spectrophotometer no.116. The comparisons confirmed that the Indian standard Dobson Ozone Spectrophotometer no.112 was in good state of calibration and the data derived from the instrument was reliable. The results of 112 with 36 are also in good agreement with each other.